Solid solubility of MgO in the calcium silicates of portland clinker. The effect of CaF2 - S. Martínez; F. Puertas; A. Palomo (Materiales de Construccion, 1992)
The solid solubility of MgO in the calcium silicates of portland clinker has been determined by XRD and XDS. The influence that the presence of CaF2 has on said solubility has also been verified. The solid solution limit of MgO in C3S at 1275 ºC lies at about 1.0% wt, where the triclinic form II stabilizes. The presence of CaF2 does not alter the maximum value of the MgO solubilized in that silicate, although there does take place the stabilization of the triclinic polymorph II at lower MgO contents (between 0.3 - 0.6% wt). The maximum amount of solubilized MgO in βC2 at 1.050 ºC lies around 0.5% wt. This value does not change by the presence of CaF2.